Molecular dynamics simulations of the transformation of carbon peapods into double-walled carbon nanotubes - Suarez-Martinez, Irene; Higginbottom, Patrick; Marks, Nigel (Pergamon, 2010)
The transformation of carbon peapods (encapsulated fullerenes in nanotubes) into doublewalled nanotubes was studied using molecular dynamics simulation. The simulations reproduce the two main trends known experimentally: the production of low-defect nanotubes and the templating effect of the outer tube. The process involves a low-temperature polymerization of the fullerenes followed by higher temperature self-assembly into a tube. Modelling of this second stage is made possible by the use of the Environment-Dependent Interaction Potential, a large number of atoms and long-time annealing. Analysis shows that the outer tube acts as a container for the self-assembly process, analogous to previous simulations and experiments in which free surfaces, either external or internal, template the formation of highly ordered sp2 phases.